Halal traceability in enhancing halal integrity for logistics industry in Malaysia: A review - Shahruddin, Mohamad I’rfan; Kamri, Nor’azzah; Sarif, Suhaili (Journal of Islamic, Social, Economics and Development, 2025)
The global acceptance of halal logistics has increased due to the demand for quality control and safety measures in halal-certified products and services. While Malaysia is a leader in the halal industry, there remains a need for improved halal traceability systems to guarantee product integrity throughout the supply chain. This paper aims to explore the principles of halal traceability that enhance halal integrity in halal logistics. A systematic review of articles published between 2013 and 2024 focused on traceability, integrity, and halal logistics, particularly third-party logistics (3PL). From an initial pool of 318 articles, 27 were identified as highly relevant. The study identifies four principles vital to developing an efficient traceability system which are halal certification (HC), documentation and halal policy (DHP), technology management (TM), and human resources (HR). Among the technologies employed, Transport Management Systems (TMS), Warehouse Management Systems (WMS), and blockchain are essential for maintaining traceability. The findings highlight that despite technology and certification risks, success depends on a well-trained workforce to manage the traceability process effectively. Thus, the study emphasises the importance of comprehensive halal certification, documentation, and the role of human resource training in strengthening halal integrity in logistics management.